Gender Economics: An Assessment - Almudena Sevilla (Institute of Labor Economics (IZA), 2020)
Concerns about gender equality have jumped to the forefront of public debate in recent years, and Gender Economics is slowly affirming its place as a major field of study. This assessment examines where we are in terms of gender equality. It reviews the theoretical foundations that can explain existing inequalities, and documents the empirical findings supported by the theories, identifying avenues for future research and providing a fruitful framework to think about the effectiveness of policies and interventions targeting gender inequality. In doing so, I provide the foundations against which the contributions in this issue can be placed.
Keywords: D31; D63; F60; 330; gender economics; gender inequality; technology; norms; policy